Advances in carbon nanomaterials for immunotherapy. (June 2022) - Azevedo, Silvana; Costa-Almeida, Raquel; Santos, Susana G.; Magalhães, Fernão D.; Pinto, Artur M.
Highlights: Nanomaterials can be used to directly modulate the immune system and CNM, namely carbon nanotubes, GBM and fullerenes offer new approaches for the enhancement of immune-based therapies against inflammatory and autoimmune diseases. SWCNT and GBM combined with NIR irradiation can target and kill tumour cells through the local increase in temperature. GBM functionalized with anti-cancer drugs or other biomolecules can activate the immune cells to kill tumour cells. Carbon nanotubes and GBM can exert a direct effect on cells, inducing ROS generation, triggering an inflammatory response, increasing pro-inflammatory cytokines production. Fullerenes can act as ROS scavengers, suppressing immune cells activation. Abstract: Remarkable advances have been achieved in the field of nanomedicine and immunotherapy, since it was found that several nanomaterials can modulate the immune system. The main objective of this review is to collect and discuss studies where carbon nanomaterials (CNM), due to their unique structure and composition, revealed to be important tools in cancer treatment, immunostimulation, and immunosuppression of inflammatory or autoimmune diseases. These materials offer several advantages, such as being effective platforms for drug delivery and targeting, immunomodulation, phototherapy, and others. Some effects still need to be upgraded and some questions persist. Positive results were already achieved, although translation to clinics is still needed. The evolution of future investigations may still revolutionize the field of biomedicine. Graphical abstract: Image, graphical abstract